Розробка і дослідження алгоритмів кластеризації для великих колекцій документів - Стех, Ю.В.; Файсал М.Е. Сардіх; Лобур, М.В.; Домброва, М.С.; Арцибасов, В.Є. (Моделювання та інформаційні технології, 2010)
This paper focuses on document clustering algorithms that build hierarchical solutions. In this paper is evaluate the performance of different criterion functions for the problem of clustering documents.